Third wheel [videorecording (DVD)] - Tamarkin, Blake; Casabianca, Anthony; Tamarkin, Jason; Tarantino, Kelsey; Lavezzi, Ricky (Gravitas Ventures, 2025)
An edgy, millennial coming-of-age breakup story following Ray, a depressed hopeless romantic who finds himself struggling with heartbreak and his return to single life, all the while living among his newly-coupled, lovestruck best friends.